RISKS OF LOSS OF STATE SOVEREIGNTY AND BALANCE OF INTERESTS UNDER THE INFLUENCE OF AGGRESSIVE FORMS OF SUPRANATIONAL CONTROL (EUROPEAN AND ASIAN LAW REVIEW, 2024)
This publication proposes for discussion the issue of the relationship between state sovereignty and supranational control is proposed for discussion. The transformation of the concept of state sovereignty in the XX – early XXI century under the influence of emerging supranational organizations and associations is demonstrated. Supranationality, being on the one hand a manifestation of state sovereignty, affects state sovereignty, limiting, changing it. The authors identify two main approaches to the definition of the term supranationality, which can be conditionally called international legal and socio-managerial.Within the framework of the first approach, supranationality is considered as supremacy over the legal system of the state, as a form of international integration. Within the framework of the socio-managerial approach, supranationality is considered through the prism of management theory.   The emergence of supranationality posed the problem of strengthening supranational control, its impact on state sovereignty and the violation of the balance of interests of the parties to international relations.  The authors distinguish three forms of supranational control. The first form is an institutional supranational control, the second form is a national supranational control carried out by one State and assumes the supremacy of one State over another. The third form is non-institutional supranational control.  The emergence of supranational control leads to the emergence of its aggressive forms aimed at eliminating state sovereignty, erasing historically established differences between nations and states, planting alien cultural values, political, economic and military pressure on states.   The authors come to the conclusion that it is necessary to counter aggressive forms of supranational control, including through the formation of information security of the state and the citizen.
Keywords: state sovereignty; supranationality; supranational control; balance of interests; globalization; information security